EXPERIENCING LEADERSHIP LIKE A COACH - Matthews, Nancy (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2016)
This note is a reflection on experiences as an educational leader, as well as provides a perspective on educational leadership, based on professional reading. It offers the metaphor of the coach, initiating a case for using a coaching philosophy as a model for a sustained form of leadership. It invites the reader to consider that with a game plan and a coaching mindset, a school can reach its full potential. EXERCER SON LEADERSHIP À LA MANIÈRE D’UN COACH Ce texte présente une réflexion sur mon expérience en tant que leader éducationnel, ainsi que ma perspective sur le sujet, basée sur des lectures professionnelles. Utilisant la métaphore du coach, il présente l’idée d’adopter une philosophie d’entraîneur pour mettre en place une forme de leadership durable. Il encourage le lecteur à considérer l’idée qu’à l’aide d’un plan de match et d’une attitude de coach, un établissement scolaire peut atteindre son plein potentiel.